Hard power, soft power, and the future of transatlantic relations - Ilgen, Thomas L. (Routledge, 2016)
The dynamics of transatlantic relations in the twenty-first century have been shaped by an American preference for the exercise of its considerable 'hard power' capabilities while Europeans have preferred to draw upon the considerable 'soft power' resources that have grown from their enviable internal processes of integration. These diverging power preferences have differential impacts on the management of Atlantic security, economic, and social and cultural relations. The contributors, long-time observers and analysts of the Atlantic partnership, debate how problematic security relations are likely to continue to be, discuss how successfully economic affairs will be managed, and examine the continuing frictions in domestic politics of social and cultural matters that should be manageable if both European and American leaders work actively and responsibly to encourage policy convergence.